Determining Factors Of Digital Wallet Usage - Nuryasman MN; Sukis Warningsih (Jurnal Manajemen, 2022)
This research aims to examine the effect of perceived usefulness, perceived risk, and trust on the usage intention of digital wallets among college students. Respondents in this study consisted of 138 undergraduate students of the Faculty of Economics and Business, Tarumanagara University, who use ShopeePay. The primary data used for the study were obtained through questionnaires distributed online, in which to select respondents a purposive sampling method was applied. Then the collected data is processed with the analysis technique of Structural Equation Modeling (SEM), using SmartPLS software. The results showed that perceived usefulness and trust positively influenced usage intention. Meanwhile, the perceived risk did not affect usage intention.